Crustal strain field in the Deccan trap region, western India, derived from GPS measurements - Reddy, C.D.; El-Fiky, Gamal; Kato, Teruyuki; Seiichi, Shimda; Kumar, K. Vijay (My University, 2000)
Global Positioning System (GPS) measurements were made to estimate the crustal deformation strain rate for the Deccan trap region, western India. Estimated horizontal velocity vectors in ITRF96 are in the range of 40–60 mm/yr with an average of 51 mm/yr in N47°E. Using the horizontal components of the velocity vectors, strain field has been estimated by the Least Square Prediction (LSP) method. An extension is observed along the west coast and south of Koyna and Warna reservoirs, transcending in to a region of compressive regime towards the interior of the shield area. The west coast geothermal province coincides with the extension regime. The collision between India and Eurasia is likely cause for compression regime. The results are discussed in conjunction with the seismo-tectonics of the study region.
Keywords: Deccan trap; GPS measurements; Least Square Prediction (LSP)